2015
DOI: 10.5194/hess-19-4041-2015
|View full text |Cite
|
Sign up to set email alerts
|

A methodological approach of estimating resistance to flow under unsteady flow conditions

Abstract: Abstract. This paper presents an evaluation and analysis of resistance parameters: friction slope, friction velocity and Manning coefficient in unsteady flow. The methodology to enhance the evaluation of resistance by relations derived from flow equations is proposed. The main points of the methodology are (1) to choose a resistance relation with regard to a shape of a channel and (2) type of wave, (3) to choose an appropriate method to evaluate slope of water depth, and (4) to assess the uncertainty of result… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 32 publications
0
19
0
Order By: Relevance
“…The most significant difference between unsteady and steady uniform flows is that the flow conditions in an unsteady flow have nonuniformity and unsteadiness. The partial derivatives of hydraulic parameters are the most relevant physical variables to describe flow unsteadiness and flow nonuniformity in 1D problems [5]. The dependence of unsteady flow resistance on derivatives (e.g., ∂u/∂t, ∂u/∂x, and ∂h/∂x) is significant [1,2].…”
Section: Analysis Of Unsteady Frictionmentioning
confidence: 99%
See 2 more Smart Citations
“…The most significant difference between unsteady and steady uniform flows is that the flow conditions in an unsteady flow have nonuniformity and unsteadiness. The partial derivatives of hydraulic parameters are the most relevant physical variables to describe flow unsteadiness and flow nonuniformity in 1D problems [5]. The dependence of unsteady flow resistance on derivatives (e.g., ∂u/∂t, ∂u/∂x, and ∂h/∂x) is significant [1,2].…”
Section: Analysis Of Unsteady Frictionmentioning
confidence: 99%
“…A significant difference was observed between steady uniform and unsteady frictions. For example, Mrokowska et al reported that the steady-state formula for frictional slope and shear velocity is not applicable to unsteady flow [5]. Fread reported that the trend of Manning coefficient vs. flow rate decreases when the inundation area is relatively small compared to an in-bank flow area, or increases in the reversed case, indicating that the Manning coefficient is a misleading parameter to investigate the relationship between resistance and flow rate [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Equation 1 contains the flow depth gradient, which is extremely difficult to determine. Mrokowska et al (2015aMrokowska et al ( , 2015b recently discussed this issue and claimed it was highly sensitive to the method used for computations. In this study, to calculate β, the variation in water depth along the flow direction (∂H/∂x) was determined from the continuous water surface profile, adjusted by a spline fitting technique to the flow depth measurements.…”
Section: Laboratory Experiments and Field Measurementsmentioning
confidence: 99%
“…A definition of bed shear stress under mobile bed conditions is not straightforward (Ferreira et al, 2012;Nikora et al, 2007), and for this reason the measurements of bed shear stress require cautious interpretation. Moreover, it should be noted that methods that may be applied under unsteady flow are scarce, mainly due to theoretical assumptions (Mrokowska et al, 2015a). Formulae derived from Saint-Venant model have become popular in unsteady flow experiments (Bombar, 2016;Song and Graf, 1996;Mrokowska et al, 2015b).…”
Section: Evaluation Of Bed Shear Stress and Stream Powermentioning
confidence: 99%